2022
DOI: 10.1111/tpj.15702
|View full text |Cite
|
Sign up to set email alerts
|

Introgression from Gossypium hirsutum is a driver for population divergence and genetic diversity in Gossypium barbadense

Abstract: During the domestication and improvement processes, interspecific introgression from Gossypium hirsutum has reorganized the genomic architecture of Gossypium barbadense; however, the introgression details and the trait-related genetic loci remain largely unknown. Here, we perform a genome-wide population analysis and genetically recategorize 365 G. barbadense accessions into four subgroups which is different from previous categorizations. A total of 315 introgression events from G. hirsutum to G. barbadense, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Also, the results indicated that mean performance for most selected families differed; these results could be due to gene expression for these families; therefore, selection for adaptable families and higher than means for better parent and commercial variety well be a help to produce high yielding recombination and earlier to grow it often winter cropping without a decrease in yield. These results are in harmony with those previously reported [33,[46][47][48][49][50]. It appeared that most of the yield and its component traits were positive and either significant or highly significant correlated with each other, indicating that these traits are essential components of cotton yield.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the results indicated that mean performance for most selected families differed; these results could be due to gene expression for these families; therefore, selection for adaptable families and higher than means for better parent and commercial variety well be a help to produce high yielding recombination and earlier to grow it often winter cropping without a decrease in yield. These results are in harmony with those previously reported [33,[46][47][48][49][50]. It appeared that most of the yield and its component traits were positive and either significant or highly significant correlated with each other, indicating that these traits are essential components of cotton yield.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated using the lint index selection to improve boll weight and seed cotton yield. Similar results were previously reported [33,36,[44][45][46] The differences between generations may be due to the various genotypes scored by each selection criteria. The analysis of variance showed highly significant differences among families of F4 for all the studied characters meaning that selection criteria would be effective.…”
Section: Discussionsupporting
confidence: 89%
“…A panel of 18 cotton genotypes, genetically diverse, was selected from the previously Characterized, genotyped, and screened germplasm (genotypes) of three cotton species (Spp. ), including; 420 Gossypium hirsutum ( Gh ) genotypes [ 40 ], 360 Gossypium barbadense ( Gb ) genotypes [ 41 ], and 215 Gossypium arboreum ( Ga ) genotypes [ 42 ] (genotype IDs are mentioned in Supplementary Table S 1 ). Six genotypes from each Spp., including three drought-tolerant and three drought susceptible genotypes, were selected based on drought tolerance indices (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Given that the introgression-of-interest in our study located on chromosome A10 of the At subgenome, we made the assumption that G. thurberi was exceedingly unlikely to be the donor for A10 introgressions, thus narrowing the field of donors to G. arboreum and G. barbadense . Following a recent reported method for identification introgression [ 26 , 31 ], we separately analyzed the introgressed fragments from G. arboreum and from G. barbadense . Fortunately, this analysis indicated that SHZDI1 shared overlap with a fragment from G. aboreum and shared no overlap with G. barbadense (Additional file 2 : Table S8), findings supporting that the introgressions are from G. arboreum.…”
Section: Resultsmentioning
confidence: 99%
“…The exotic introgression analysis followed a previously described procedure [ 26 , 31 ]. The two potential donors for introgressed fragments, G. barbadense and G. arboreum , were evaluated in the introgression analysis.…”
Section: Methodsmentioning
confidence: 99%